Determinants of FDI inflows in advanced economies: Does the quality of economic structures matter? - Konstantinos Dellis; David Sondermann; Isabel Vansteenkiste (European Central Bank (ECB), 2017)
This paper investigates the role of economic structures as determinants of FDI inflows. We expand on the existing literature by focusing on advanced economies, using a newly available measure of FDI which cleans the data from statistical artefacts, such as financial round tripping, and by relying on a wide variety of measures that proxy the quality of a country's economic structures. Our results show that there is an empirical relation from the quality of a host country's economic structures to FDI inflows. These results are robust to various economic specifications and are confirmed when restricting our sample to euro area countries only.
Keywords: F21; F23; L51; O43; 330; Foreign direct investment; economic structures; institutions; euro area countries